Anisotropy and enhancement of thermoelectric performance of Sr0.8La0.067Ti0.8Nb0.2O3−δ ceramics by graphene additions. Issue 42 (15th October 2019) - Srivastava, D.; Norman, C.; Azough, F.; Ekren, D.; Chen, K.; Reece, M. J.; Kinloch, I. A.; Freer, R.
Abstract : Orientation of graphene platelets in SrTiO3 ceramic composites leads to significant anisotropy in electrical conductivity and thermal conductivity. Abstract : A-site deficient SrTiO3 ceramics are very promising n-type oxide thermoelectrics but currently limited by their low performance compared to more conventional materials. We show that incorporation of graphene or graphene oxide can significantly improve the transport properties and hence ZT of the ceramic matrix. Powders of Sr0.8 La0.067 Ti0.8 Nb0.2 O3− δ were prepared by the mixed oxide route; ceramics and composites with ≤3 wt% graphene or graphene oxide were densified by spark plasma sintering (SPS) at 1473 K for 5 minutes. The microstructures obtained were uniform with an average grain size of 5 μm; the carbon additions were uniformly distributed. Composites employing 'as-prepared' powders exhibited three orders of magnitude increase in electrical conductivity, a reduction in thermal conductivity from 4.00 to 2.64 W m −1 K −1, but very modest thermoelectric figure of merit ( ZT ) values, less than 0.1. Graphene additions yielded superior thermoelectric performance to graphene oxide. Composites prepared with 'pre-reduced' oxide powders and 1 wt% graphene were at least 99% dense, with further improvement in electrical conductivity. There was strong anisotropy in their transport properties due to the alignment of the graphene flakes perpendicular to the pressing direction; electrical conductivity was significantly higher perpendicular to the pressing direction; thermal conductivity was lowest parallel to the pressing direction. The highest thermoelectric figure of merit (∼0.25 at 1000 K) was achieved for samples containing graphene measured parallel to the pressing direction. The control of thermoelectric transport properties by additions of carbon species, and the resulting anisotropy in properties could guide the development of processing routes to produce future target materials.